Fundamental Of Entrepreneurship (ENT300) : Prima Utama Jaya Sdn. Bhd. constructions, supplies & services company/ Nicodemus Mark Marek … [et al.] - Mark Marek, Nicodemus; Raya, Nur Khairunnisa Suhada; Anuar, Mohd Haafiz (2017)
This case study is a research and review the development of a company . For this case study we will review a construction and service company which is PRIMA UTAMA JAYA SDN. BHD. This study investigated the company in term of it achievement, strength, weaknesses, opportunities, threat and recommend the solutions and how to improve the business.PRIMA U'£AMA JAYA SDN. BHD. is a multipurpose company since they run a business'behalf of constructions, supplies and services. They do construction of building and road, supply constructions materials and lab equipment. In addition, they also provided service ofoffice cleaning , grass cutter and drainage clearing.